2023
DOI: 10.1172/jci164185
|View full text |Cite
|
Sign up to set email alerts
|

The gut signals to AGRP-expressing cells of the pituitary to control glucose homeostasis

Abstract: Departments of Medicine (1), Neuroscience (2) and Molecular Pharmacology (3)

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 82 publications
0
5
0
Order By: Relevance
“…Recently, Liu et al 5 . demonstrated that cells in the pituitary gland express an AGRP splice variant crucial for modulating systemic glucose metabolism in non‐genetically obese mice 5 .…”
Section: Figurementioning
confidence: 99%
See 3 more Smart Citations
“…Recently, Liu et al 5 . demonstrated that cells in the pituitary gland express an AGRP splice variant crucial for modulating systemic glucose metabolism in non‐genetically obese mice 5 .…”
Section: Figurementioning
confidence: 99%
“…Next, to examine whether suppression of AGRP‐B cells affects glucose tolerance, Liu et al 5 . performed experiments in two murine models; Agrp‐B KO mice and AGRP‐B silenced mice.…”
Section: Figurementioning
confidence: 99%
See 2 more Smart Citations
“…Apart from incretins, other postprandial signals have also been involved in regulating glucose and lipid metabolism via the CNS. For instance, FGF19, a postprandial enterokine that has hypoglycemic effects, elicits its effects by modulating both hypothalamic and brainstem neuronal populations to improve glucose homeostasis [ 289 , 290 , 291 , 292 ]. Amylin’s effects on food intake and body weight were demonstrated to be dependent on modulation of brainstem neuronal signaling, specifically lateral dorsal tegmental nucleus, resulting in increased SNS activity to BAT [ 293 ].…”
Section: Crosstalk Between Hypothalamic and Brainstem Nuclei With Met...mentioning
confidence: 99%